The Effect Earning Per Share (EPS), Return on Equity (ROE), and Debt to Equity Ratio (DER) Toward Stock Return with dividend policy as Intervening Variable (Case study on Transportation and Logistics Sector Companies Listed in The Indonesia Stock Exchange - Trisnawati Nur Hikmah; Cepi Pahlevi; Kasman Damang (Hasanuddin Journal of Applied Business and Entrepreneurship, 2022)
Earning per share (EPS) shows the profit that is entitled to each shareholder of one share of common stock. The debt to equity ratio shows the company's ability to pay debts with its equity. The higher return on equity (ROE) shows the company's performance is getting better and has an impact on the company's stock price. ROE is not a true measure of shareholder return because it does not take into account dividends and capital gains for shareholders. Return is the result obtained from the investment or the level of profit enjoyed by the investor on an investment he does. An investor who invests funds in securities cannot only look at the trend of stock prices. Dividend Payout Ratio (DPR) is the percentage of profits distributed in the form of cash dividends. The purpose of this study was to determine the effect of Earning per Share (EPS), Return on Equity (ROE), Debt to Equity Ratio (DER) on Stock Return with Dividend Policy as an Intervening Variable. The population of this study is the transportation and logistics sector companies listed on the Indonesia Stock Exchange in 2016-2020. The samples taken were 34 samples. The sampling technique used was the purposive sampling technique. The analytical method used multiple linear regression analysis with SPSS software version 21 which is supported by the classical assumption test. This research used is the Sobel test. The results show earnings per share (EPS) have a significant positive effect on dividend policy, return on equity (ROE) and debt to equity ratio (DER) have a significant negative effect on dividend policy, dividend policy (DPR) have a significant negative effect on stock returns, earnings per share (EPS) have an insignificant negative effect on stock returns, return on equity (ROE) and debt to equity ratio (DER) has an insignificant positive effect on stock returns, the dividend payout ratio (DPR) cannot mediate the effect of earnings per share (EPS) on stock returns, the dividend payout ratio (DPR) mediate the effect of return on equity and debt to equity ratio (DER) on stock returns.